2021
DOI: 10.3390/ani11061538
|View full text |Cite
|
Sign up to set email alerts
|

Chestnut Shell Tannins: Effects on Intestinal Inflammation and Dysbiosis in Zebrafish

Abstract: The aim of the present study was to test the possible ameliorative efficacy of phytochemicals such as tannins on intestinal inflammation and dysbiosis. The effect of a chestnut shell (Castanea sativa) extract (CSE) rich in polyphenols, mainly represented by tannins, on k-carrageenan-induced intestinal inflammation in adult zebrafish (Danio rerio) was tested in a feeding trial. Intestinal inflammation was induced by 0.1% k-carrageenan added to the diet for 10 days. CSE was administered for 10 days after k-carra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 126 publications
3
12
1
Order By: Relevance
“…Mango supplementation in mice fed with a high-fat diet can prevent the loss of beneficial intestinal bacteria, especially Bifidobacteria, Akkermansia, and Aldercrutzia [ 47 ]. Orso applied a diet of chestnut shell extract rich in tannin to a zebrafish intestinal inflammation model and found that it promoted the growth of healthy and beneficial bacteria ( Enterobacteriaceae and Pseudomonas ) [ 48 ]. Supplementation with polyphenols can also change the ratio of Firmicutes to Bacteroides .…”
Section: Impact Of Dietary Polyphenols On Gut Microbiotamentioning
confidence: 99%
“…Mango supplementation in mice fed with a high-fat diet can prevent the loss of beneficial intestinal bacteria, especially Bifidobacteria, Akkermansia, and Aldercrutzia [ 47 ]. Orso applied a diet of chestnut shell extract rich in tannin to a zebrafish intestinal inflammation model and found that it promoted the growth of healthy and beneficial bacteria ( Enterobacteriaceae and Pseudomonas ) [ 48 ]. Supplementation with polyphenols can also change the ratio of Firmicutes to Bacteroides .…”
Section: Impact Of Dietary Polyphenols On Gut Microbiotamentioning
confidence: 99%
“…The histological analysis was achieved as described by Orso et al [21]. Specifically, intestine samples were fixed for 24 h at 4 • C in 4% formalin (pH 7.4) prepared in 0.01 M PBS (phosphate-buffered saline).…”
Section: Histological Analysismentioning
confidence: 99%
“…Dehydration in a series of increasing ethanol grades and clarification with xylene were performed prior to embedding tissues in paraffin. Embedded samples were cut with a microtome (Leica Microsystems, Wetzlar, Germany) into 5 µm sections, and, as reported by Orso et al [21], anatomically comparable sections of the mid-intestine were selected to be deparaffinized and stained with hematoxylin and eosin (H&E) or Alcian blue to perform morphological analyses and count of the number of goblet cells, respectively. A Leica DMI6000 light microscope equipped with a Leica DFC340 digital camera (Leica Microsystems, Wetzlar, Germany) was used to analyze the stained intestinal sections at 20X and 40X magnifications.…”
Section: Histological Analysismentioning
confidence: 99%
See 2 more Smart Citations